Labour Costs and the Decision to Hire the First Employee - Bart Cockx; Sam Desiere (Institute of Labor Economics (IZA), 2023)
Firms without paid employees account for up to 80% of all firms, but only a small minority ever hires. This paper investigates the relationship between labour costs and the decision to hire a first employee and become an employer. Leveraging a unique policy in Belgium that permanently reduced the labour cost of the first employee by 13%, we find that the number of new, first-time employers jumped by 31% immediately following the reform. The elasticity of the probability to hire the first employee with respect to the labour cost is -2.39 [95% CI: -3.45, -1.25].
Keywords: D22; H25; J08; J23; L26; M13; 330; nonemployers; hiring decisions; payroll taxes; small businesses